Economic analysis of tissue cultured banana (Musa × paradisiaca) production under the influence of integrated nutrient management - HAZARIKA, T K; NAUTIYAL, B P; BHATTACHARYYA, R K (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted to evaluate various integrated nutrient management packages to evaluate the yield, quality and economics of banana (Musa × paradisaca L.) cultivation during 2008-2010. The response of INM on economics of tissue cultured banana cv. Grand Naine indicated that the overall cost of cultivation as well as economics of banana production was significantly influenced by integration of biofertilizers, organic manure and inorganic fertilizers. Among the different treatments, highest expenditure of ₹ 264 110.00 per ha was incurred in 100% RDF + VAM + Azospirillum + PSB + Trichoderma harzianum. However, the same treatment recorded the highest gross as well as net income. In spite of maximum cost of cultivation, the highest cost benefit ratio of 4.22:1 was also recorded in this treatment, followed by 75% RDF +VAM + Azospirillum + PSB + Trichoderma harzianum.